Corporate social responsibility and repurchase intentions: The parallel mediation of consumer satisfaction and consumer trust - Albert John; Nisar Ahmad; Gulnaz Shahzadi; Faisal Qadeer; Afia Khalid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
Sustaining desired consumer behaviors is challenging for marketers. Organizations adopt various marketing strategies to retain their consumers, yet the role of corporate social responsibility (CSR) in this regard has been generally overlooked. The current study investigates the relationship between CSR and repurchase intentions of the individual consumer. Drawing on the social exchange theory, we argue that the link between CSR and repurchase intentions is not linear. The study proposes the parallel mediation of customer satisfaction and customer trust to explain this relationship. A mall intercept survey was conducted to collect data from 230 customers of four brands familiar with the respective advertisements and CSR initiatives of these brands. We used Hayes Macro in SPSS using 5000 bootstrap samples to test the proposed model. The results reveal that CSR plays its part in shaping the repurchase intention. The results also support the parallel mediation of consumer satisfaction and trust. It is one of the initial studies that empirically test a holistic framework to realize the role of CSR in developing repurchase intentions. The study contributes to the literature on consumer behavior and social exchange theory by providing empirical evidence from a developing country perspective.
Keywords: 330; CSR; repurchase intentions; customer satisfaction; customer trust; mallintercept survey; social exchange theory; Pakistan